2009
DOI: 10.1159/000235581
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Long-Term Consumption of Milk Supplemented with Probiotic Lactobacilli and Fluoride on Dental Caries and General Health in Preschool Children: A Cluster-Randomized Study

Abstract: The aim of this study was to evaluate the effect of milk supplemented with probiotic bacteria and fluoride on caries development and general health in preschool children. Children 1–5 years of age (n = 248) attending 14 day care centres with 27 units in northern Sweden entered the study. The centres were randomly assigned to two parallel groups: children in the intervention group were served 150 ml milk supplemented with Lactobacillus rhamnosus LB21 (107 CFU/ml) and 2.5 mg fluoride per litre for lun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
89
1
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 143 publications
(101 citation statements)
references
References 44 publications
3
89
1
4
Order By: Relevance
“…Various clinical studies have shown that L. rhamnosus and L. paracasei consumption could reduce S. mutans biofilm formation in the oral cavity [15,30]. Despite the extensive research effort devoted to determining the effects of LAB supplementation on cariogenic bacteria, there are still large knowledge gaps related to understanding the mechanism of the bacterial behavior in response to supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical studies have shown that L. rhamnosus and L. paracasei consumption could reduce S. mutans biofilm formation in the oral cavity [15,30]. Despite the extensive research effort devoted to determining the effects of LAB supplementation on cariogenic bacteria, there are still large knowledge gaps related to understanding the mechanism of the bacterial behavior in response to supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown positive effects of probiotic lactobacilli: reduction in the number of mutans streptococci, dental plaque and gingival inflammation [Nikawa et al, 2004;Krasse et al, 2006;Calgar et al, 2008;Marttinen et al, 2012]. To date, however, only five studies have been published with caries as the endpoint [Näse et al, 2002;Stecksén-Blicks et al, 2009;Petersson et al, 2011;Hasslöf et al, 2013;Taipale et al, 2013], three of which report lower caries increment after exposure to probiotic bacteria compared to control groups. In the study by Näse et al [2002], preschool children were exposed to milk with L. rhamnosus five days a week over seven months at 1-6 years of age.…”
mentioning
confidence: 99%
“…31,32 Both studies found improvements in general health, along with reductions in caries risk and caries incidence, but the most important findings were probably those related to the use of less prescribed antibiotics. 32,34 In fact, the findings may support a "metabolic domino effect" in which probiotic therapy is a link between oral and general health; the oral cavity influences and is influenced by general health. Future research will reveal if orally derived probiotic candidates optimized for oral diseases may have a similar dual impact.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] The first of these studies investigated the effects of probiotic bacteria given to 594 preschool children aged 1-6 years, and showed a significant reduction in caries increment in the probiotic milk group after 7 months, compared to the control group, but only in the subgroup of the 3-4 year-olds. 31 It was claimed that the 5-day-aweek intake of probiotic milk reduced the risk of caries significantly (OR = 0.56).…”
Section: Clinical Trials With Caries Endpointmentioning
confidence: 99%
See 1 more Smart Citation